Village Fund Allocation and Community Development Practices in Rangkah Kidul - Arik Atus Solikah; Isna Fitria Agustina (Indonesian Journal of Cultural and Community Development, 2025)
General Background: Village funds constitute a central policy instrument for supporting rural development and community welfare in Indonesia. Specific Background: In Rangkah Kidul Village, these funds have been allocated to physical infrastructure and non-physical programs such as health services, social assistance, and community empowerment. Knowledge Gap: Existing studies often emphasize financial outcomes, while limited attention is given to how village fund allocation is realized in daily governance practices and perceived by the community. Aims: This study aims to describe the utilization of village funds in supporting development activities and community programs in Rangkah Kidul Village, Sidoarjo Regency. Results: Using a qualitative descriptive approach through interviews, observation, and documentation, the findings show that village fund allocation aligns with development priorities, particularly infrastructure provision, health services, and social assistance, although challenges remain in human resource capacity and administrative procedures. Novelty: This study offers contextual insight into village-level governance by integrating community perceptions with program implementation processes. Implications: The findings provide practical references for village governments to improve participatory planning, administrative readiness, and sustainable community development practices.